KESESUAIAN RENCANA TATA RUANG WILAYAH TERHADAP RESIKO BENCANA ROB DAN GENANGAN DI WILAYAH PESISIR KOTA SEMARANG - Vicky Rasyiid Maulana; Imam Buchori (Teknik PWK (Perencanaan Wilayah Kota), 2016)
Floods and puddle disaster are one of the natural disaster or natural phenomenon that potentially caused devastation consequences, happened in certain condition, time and location. Floods and puddle disaster in the coast of semarang is a phenomenon that happened once a year. It influenced by the instruction of sea water, land subsidence, poor drainage and the factor of high rain fall during rainy season. As in a solution to cope with floods and puddle disaster-prone area, the government of semarang has made a plan for disaster-prone area that listed in RTRW in Semarang. The purpose of this research is to learn how suitable is the layout plan of floods and puddle disaster risk in the coastal area of semarang. This research uses quantitative approach with data analysis method in the form of scoring analysis, quantitative descriptive and spatial analysis. In determining of this RTRW suitability is carried on in several stages of analysis which is one of them are tidal flood disaster prone analysis and inundation hazard, vulnerability of physical condition and risk of tidal flood and puddle on coast of Semarang City. Disaster prone analysis is the study of research measured by topography level, rainfall, soil type and land used. Vulnerability analysis of physical conditions are the research study measured by road levels, drainage, watershed and river density, soil deflation and building solidity. Whereas, risk analysis of tidal flood disaster and puddle are the result of disaster prone analysis with vulnerability of physical condition on coast of Semarang City. The result of this research is obtained that around 84% of land area used on coast of Semarang City (12894,09 Ha) suitable with RTRW . Land area used is one of way to minimize risk of rob disaster and inundation.  Whereas, 16% of land area used on coast of Semarang City is not suitable due to it doesn’t have effort to minimize risk of disaster tidal flood and puddle. Therefore, Concluded that the most potential rob area are industrial areas, transportation service areas, educational areas, Economic areas, sport and recreation and open green spaces of all.